Education for sustainability development via school garden - Papadopoulou, Aikaterini; Kazana, Athina; Armakolas, Stefanos (European Journal of Education Studies, 2020)
The garden can be viewed as an imitation of nature in an urban setting. In past times, many educators aware of the importance of nature in the education process were avid supporters of the school garden. Many studies that examined the influence of the school garden in the education process have shown that it offers multiple benefits to the students, one of which is that it furthers experiential learning. Students involved in gardening improve their overall academic performance and increases their interest in learning. It also seems to have positive effects on their overall behavior and on their emotional and social health. In the results of studies, we can also see the students who participated in gardening showed remarkable improvement in their overall physical health, and that they often adopted better nutritional habits. Finally, the school garden can serve as a portal for the students and for the school in general, to introduce them to environmental education and to sustainability in both theory and practice.  Article visualizations:
Keywords: education; school garden; sustainability